Resonance assignments of non-exchangeable protons in B type DNA oligomers, an overview. - van de Ven, F J (1988)
The chemical shifts of 1H resonances of non exchangeable protons (except H5', H5" and adenine H2) of over six hundred nucleotides have been collected. The influence which the base of the nucleotide itself as well as the bases on its 5' and 3' side exert on the chemical shifts of the various resonances has been investigated. Most of the resonances appear to be predominantly influenced by only one base. For H2', H2", H3', H4' and H6/H8 this is the base of the central nucleotide, for H5(C) and CH3(T) it is the one on the 5' side and for H1' it is the one on the 3' side. Chemical shift distribution profiles are presented which allow an estimation of the probability of finding a particular resonance at a particular position in the spectrum.